IRON-RICH FOOD CONSUMPTION AND ASSOCIATED FACTORS AMONG CHILDREN AGED 6-23 MONTHS: A FURTHER ANALYSIS OF 2017 INDONESIA DEMOGRAPHIC AND HEALTH SURVEYS - Akhyudi, Dewi Muthia Charissa; Astutik, Erni; Ismail, Wan Ismahanisa (Universitas Airlangga, 2024)
Iron deficiency in children age under two years are potentially to get a higher risk of iron deficiency anemia. This research seeks to examine the factors that influencing the consumption of iron-rich food among aged group 6-23 months in Indonesia. This research utilized a cross-sectional design and was conducted through a secondary analysis of 2017 Indonesia Demographic Health Survey (IDHS) data, involving a total weighted sample of 4.622 children aged group 6-23 months. The process of analysis data using a computer program. The statistical test used for bivariable analysis is the chi-square test and multivariable analysis uses the logistic regression test. Overall, 71.7% of children aged group 6-23 months in Indonesia exhibited a strong level of consumption of iron-rich foods. Children with aged 18-23 months [aPR= 8.42; 95%CI= 6.61-10.72], highly educated mothers [aPR= 1.14; 95%CI= 1.01-1.98], antenatal care visits <6 times [aPR= 1.77; 95%CI= 1.04-3.02], who took medication for deworming and antiparasitic over the past 6 months [aPR= 1.55; 95%CI= 1.17-2.05], children who were not breastfeeding [aPR= 1.36; 95%CI= 1.10-1.68], relatively rich economic status [aPR= 1.43; 95%CI= 1.11-1.82] and mothers who access of mass media [aPR= 1.40; 95%CI= 1.17-1.68] has a statistically significant with the good consumption of iron-rich foods in children aged 6-23 months in Indonesia. The interventions must have been focused on nutrition education, access to antenatal care (ANC), encouraging health promotion through mass media and support efforts from government to improving socioeconomic factors are needed for increase the consumption of iron-rich foods in children.